IMPLEMENTASI METODE PEMBELAJARAN EFEKTIF DI SEKOLAH DASAR - Randi Purnama (Jurnal At-Tabayyun, 2019)
Basic education has a strong influence on the generation of children, because the child's brain at this time is very active in recording everything that is seen, listened to and in its motion. Therefore basic education is a great place to cultivate the seeds of a child's positive character. Remembering to cultivate a child's character takes a short, consistent, and involved all academic and parental civitas. The role of teachers and parents is very influential in growing and developing the child's potential and character. Through learning in the school a child develops all aspects of it, therefore an educator must be able to create an effective learning method to achieve the desired goal. Choosing and establishing the right and effective learning methods in elementary schools is an alternative to motivating students to be able to apply their knowledge and experience and achieve their goals. Some effective learning methods for elementary school according to al-Ghazali and Ibn Khaldun such as, see the level of the power of the children, the material delivery is gradually, the importance of habituation, and the presentation of concrete illustrations or called Demonstration. Demonstrations in the application of learning require media demonstrations or experiments. Then to support the success in carrying out the method of learning a teacher must have the personality traits and characteristics of true educators, according to al-Ghazali, teachers who can be endowed teaching assignments are teachers who are besides intelligent and perfect wits, also his good teacher and his physical strength.